Performance of Oreochromis niloticus in recirculating aquaculture systems at different levels of daily protein intake. (19th August 2019) - Fimbres‐Acedo, Yenitze E.; Garza‐Torres, Rodolfo; Endo, Masato; Servín‐Villegas, Rosalía; Fitzsimmons, Kevin M.; Emerenciano, Maurício G. C.; Magallón‐Barajas, Francisco J.
Abstract: Recirculating aquaculture systems (RASs) are an efficient method for developing sustainable aquaculture and the development of a feed strategy for RASs could be a key factor for the success of culturing Oreochromis niloticus . The daily protein intake (DPI) mathematical function related to body weight (BW) was designed (DPI = −3.818 ln (BW) + 30.158) named DPI 1.0 = 100%. Three feeding rates were established, DPI 1.4, 1.2 and 1.0, and were implemented in an RAS production cycle (100 fish/m 3 ) for 34 weeks. The final growth measurements were 908.0 ± 57.9 g (DPI 1.4), 887.0 ± 113.5 g (DPI 1.2) and 702.2 ± 38.1 g (DPI 1.0) ( p < .05), with feed conversion rates (FCRs) of 2.3, 1.9 and 1.9, respectively; the survival was ≥ 98.3% ( p > .05) for all treatments. DPI levels conditioned the growth of the fish and the proportion of lipid: protein in the bodies of O. niloticus but not in the fillets. The mathematical function DPI 1.2 = 120% (DPI = −4.582 ln (BW) + 36.19) used in the RAS at the 40% protein level improved fish growth, the protein efficiency ratio and FCRs. The DPI values were estimated for 49 different cases and feeding strategies showed lower values than most of the different DPI mathematical functions used and cited in this work. Therefore, DPI metric is a good tool that provides the specific requirements of protein for O. niloticus growth, which can enable farmers to ration feed and improve energy use (kWh/ fish) and facilitate the integration of RAS with horticulture.